2016
DOI: 10.1097/fbp.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between aggression, empathy skills and serum oxytocin levels in male children and adolescents with attention deficit and hyperactivity disorder

Abstract: Although attention deficit and hyperactivity disorder (ADHD) are recognized as neurodevelopmental disorders characterized by impairment in executive functions, impairments in social functioning are often accompanied by ADHD. Oxytocin (OT) has been investigated in a number of psychiatric disorders owing to its effects on social interactions. The aim of this study was to determine the relationship between aggression, empathy and OT levels in children with ADHD. Forty male patients with ADHD, ranging in age from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 55 publications
(62 reference statements)
1
23
0
Order By: Relevance
“…Furthermore, OT has been associated with resilience in high‐risk contexts at this age. Attenuated salivary OT was found in 7–15‐year‐old children with separation anxiety that increased following sensitive mother–child interaction (Lebowitz et al., ); 9–11‐year‐old children exposed to chronic trauma exhibited lower OT only when their mothers sensitive parenting was low (Ulmer‐Yaniv et al., ); lower serum OT levels were found in children with ADHD and higher OT correlated with lower impulsivity and aggression and more empathy in these children (Demirci, Ozmen, Kilic, & Oztop, ; Demirci, Özmen, & Öztop, ); and children's plasma and cerebrospinal fluid OT concentrations predicted lower anxiety (Carson et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, OT has been associated with resilience in high‐risk contexts at this age. Attenuated salivary OT was found in 7–15‐year‐old children with separation anxiety that increased following sensitive mother–child interaction (Lebowitz et al., ); 9–11‐year‐old children exposed to chronic trauma exhibited lower OT only when their mothers sensitive parenting was low (Ulmer‐Yaniv et al., ); lower serum OT levels were found in children with ADHD and higher OT correlated with lower impulsivity and aggression and more empathy in these children (Demirci, Ozmen, Kilic, & Oztop, ; Demirci, Özmen, & Öztop, ); and children's plasma and cerebrospinal fluid OT concentrations predicted lower anxiety (Carson et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…As this line of research has developed, so has the interest in the therapeutic potential of OT to treat a range of psychological disorders that are characterised by deficits in these social behaviours. Indeed research has shown that several of these disorders (autism spectrum disorder [9], attention deficit hyperactivity disorder [10], and depression [11]) are associated with disrupted OT systems, and that intranasal OT administration can attenuate (to some extent) the characteristic empathy deficits [12, 13]. Thus prior research has shown that specific psychological disorders show a deficit in cognitive empathy, and that cognitive empathy can be moderated by OT.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the age of the study group was selected from 6 to 12 years old. This was guided by studies in literature which studied behavioral problems and cognition in ADHD [22,23].…”
Section: Discussionmentioning
confidence: 99%